Analysis of Improved In-Cylinder Combustion Characteristics with Chamber Modifications of the Diesel Engine - Doppalapudi, AT; Azad, AK; Khan, MMK (MDPI AG, 2023)
This study numerically analyses the effects of chamber modifications to investigate the improvement of in-cylinder combustion characteristics of the diesel engine using a computational fluid dynamics (CFD) approach. Five different modified chambers, namely, the double swirl combustion chamber (DSCC), bathtub combustion chamber (BTCC), double toroidal re-entrant combustion chamber (DTRCC), shallow depth combustion chamber (SCC), and stepped bowl combustion chamber (SBCC) were developed and compared with a reference flat combustion chamber (FCC). The effects of chamber modifications on temperature formation, velocity distribution, injection profiles, and in-cylinder turbulent motions (swirl and tumble ratio) were investigated. During the compression stroke, near top dead centre, the SCC showed a peak temperature of 970 K, followed by the FCC (968 K), SBCC (967 K), and DTRCC (748 K to 815 K). The DSCC and the SCC showed a high swirl ratio above 0.6, whereas the DTRCC and the BTCC showed a high tumble ratio of approximately 0.4. This study found that the SCC, BTCC, and DSCC have better combustion rates than the FCC in terms of temperature, heat release rate, and velocity distribution. However, the DTRCC showed poor temperature formation rates and rapid heat release rates (approx. 150 J/°CA), which can lead to rapid combustion and knocking tendencies. In conclusion, the DSCC and the SCC showed better combustion rates than the other chambers. In addition, turbulent motions inside the chambers avoided combustion in crevice regions. This study recommends avoiding chambers with wider bowls in order to prevent uneven combustion across the cylinder. Furthermore, split bowls such as the DSCC, along with adjusted injection rates, can provide better results in terms of combustion.
Keywords: 40 Engineering; 4017 Mechanical Engineering; 4002 Automotive Engineering; 02 Physical Sciences; 09 Engineering; 33 Built environment and design; 40 Engineering; 51 Physical sciences